Socialization and Coaching Science Training at KONI Surakarta Coaches in 2024 - Prasetyo, Hendrig Joko; Purnama, Sapta Kunta; Doewes, Rumi Iqbal; Hidayatullah, Mohammad Furqon; Nuryadin, Islahuzzaman; Haris Nugroho; Slamet Widodo; Fadilah Umar (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
Coaching is a very complex process and coaches are required to do various things such as in-depth training and competition planning, organizational tasks, and mentoring athletes, which goes beyond just teaching skills and tactics. A coach's ability to achieve these key expectations will likely determine their coaching effectiveness. Therefore, this devotion is carried out with the aim of providing knowledge and training regarding coaching science to coaches so that coaches are able to carry out appropriate training for their athletes. The devotion method is carried out with socialization and coaching science training. Devotion partners are KONI Surakarta coaches from 14 sports, totaling 20 coaches aged 29.20 ± 9.66 years and have coaching experience of 3.97 ± 4.87 years. Evaluation is carried out on the coaches' knowledge. The devotion results show that the coaches' knowledge about coaching science has increased, seen from the pretest percentage of 35.00% and posttest 65.00%. So it can be concluded that KONI Surakarta coaches have knowledge in coaching science which can be applied in implementing training.